2012
DOI: 10.1016/j.bbalip.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen weeks of dietary n-3 polyunsaturated fatty acid deprivation increase turnover of n-6 docosapentaenoic acid in rat-brain phospholipids

Abstract: Docosapentaenoic acid (DPAn-6, 22:5n-6) is an n-6 polyunsaturated fatty acid (PUFA) whose brain concentration can be increased in rodents by dietary n-3 PUFA deficiency, which may contribute to their behavioral dysfunction. We used our in vivo intravenous infusion method to see if brain DPAn-6 turnover and metabolism also were altered with deprivation. We studied male rats that had been fed for 15 weeks post-weaning an n-3 PUFA adequate diet containing 4.6% alpha-linolenic acid (α-LNA, 18:3n-3) or a deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…We and others have previously shown that increased brain content of DPA n-6, together with reduced brain DHA content, is associated with behavioral impairment in adult rodents fed with diet deprived of n-3 PUFAs (Lim et al, 2005a;Mingam et al, 2008;Lafourcade et al, 2011;Igarashi et al, 2012;Larrieu et al, 2012;Moranis et al, 2012;Larrieu et al, 2014). Of note, in all these studies, n-3 PUFA deficiency started early in life, covering the in utero and lactation period.…”
Section: )mentioning
confidence: 90%
“…We and others have previously shown that increased brain content of DPA n-6, together with reduced brain DHA content, is associated with behavioral impairment in adult rodents fed with diet deprived of n-3 PUFAs (Lim et al, 2005a;Mingam et al, 2008;Lafourcade et al, 2011;Igarashi et al, 2012;Larrieu et al, 2012;Moranis et al, 2012;Larrieu et al, 2014). Of note, in all these studies, n-3 PUFA deficiency started early in life, covering the in utero and lactation period.…”
Section: )mentioning
confidence: 90%
“…As noted in the Introduction, K* represents combined diffusional and enzymatic steps involved in DHA incorporation from plasma into brain phospholipid, replacing the DHA that has been metabolically lost [18], [20], [21]. K* was increased when plasma DHA concentration was reduced by severe (three generations) or moderate (12 weeks in one generation) dietary n-3 PUFA restriction in rats [12], [44]. Although we did not detect a lower plasma DHA concentration in the alcoholics at the scan time, with their typically poor dietary habits and frequent liver dysfunction, chronic alcoholics often have reduced plasma concentrations [45].…”
Section: Discussionmentioning
confidence: 99%
“…Females were mated with normal-chow fed males and placed on diets adequate (ADQ) or deficient (DEF) in n-3 PUFAs (Dyets Inc., Bethlehem, PA) (3235). First generation (G1) rats were weaned at post-natal day (PND) 21, and males were tested on behavioral tasks.…”
Section: Methodsmentioning
confidence: 99%